Prevalence and variability of siderophore production in the Achromobacter genus - P. Sorlin; E. Brivet; V. Jean-Pierre; F. Aujoulat; A. Besse; C. Dupont; R. Chiron; E. Jumas-Bilak; Q. Menetrey; H. Marchandin (Microbiology Spectrum, 2024)
ABSTRACTAchromobacter spp. are opportunistic pathogens of environmental origin increasingly isolated in patients with underlying conditions like cystic fibrosis (CF). Despite recent advances, their virulence factors remain incompletely studied, and siderophore production has not yet been investigated in this genus. The aim of this study was to evaluate the production of siderophores in a large collection of Achromobacter spp. and evaluate the variability according to the origin of the strain and species. A total of 163 strains were studied, including 128 clinical strains (CF and non-CF patients) and 35 strains of environmental origin. Siderophores were quantified by the liquid chrome azurol-sulphonate assay. Species were identified by nrdA gene-based phylogeny. Strains were assigned to 20 species, with Achromobacter xylosoxidans being the most represented (51.5% of strains). Siderophore production was observed in 72.4% of the strains, with amounts ranging from 10.1% to 90% siderophore units. A significantly higher prevalence of siderophore-producing strains and greater production of siderophores were observed for clinical strains compared with strains of environmental origin. Highly variable observations were made according to species: A. xylosoxidans presented unique characteristics (one of the highest prevalence of producing strains and highest amounts produced, particularly by CF strains). Siderophores are important factors for bacterial growth commonly produced by members of the Achromobacter genus. The significance of the observations made during this study must be further investigated. Indeed, the differences observed according to species and the origin of strains suggest that siderophores may represent important determinants of the pathophysiology of Achromobacter spp. infections and also contribute to the particular epidemiological success of A. xylosoxidans in human infections.IMPORTANCEAchromobacter spp. are recognized as emerging opportunistic pathogens in humans with various underlying diseases, including cystic fibrosis (CF). Although their pathophysiological traits are increasingly studied, their virulence factors remain incompletely described. Particularly, siderophores that represent important factors of bacterial growth have not yet been studied in this genus. A population-based study was performed to explore the ability of members of the Achromobacter genus to produce siderophores, both overall and in relevant subgroups (Achromobacter species; strain origin, either clinical—from CF or non-CF patients—or environmental). This study provides original data showing that siderophore production is a common trait of Achromobacter strains, particularly observed among clinical strains. The major species, Achromobacter xylosoxidans, encompassed both one of the highest prevalence of siderophore-producing strains and strains producing the largest amounts of siderophores, particularly observed for CF strains. These observations may represent additional advantages accounting for the epidemiological success of this species.